Application of Problem-Solving Learning to Improve Mathematics Learning Outcomes in Elementary Schools - Achadi, Budi Santosa (PEDAGOGIKA, 2023)
The application of learning "problem solving" to the subject matter of mathematics in elementary schools has been proven to improve student learning outcomes. Through the action research approach, the data collection method is based on an assessment that measures student learning outcomes. The findings of this study indicate that the problem-solving learning paradigm can be an effective tool in which fourth grade students can improve their mathematics learning outcomes, especially in the sub-field of fractions. Only 36.36% of the pre-cycle implementation of most of the student learning objectives that have been achieved, the fact that the proportion of student learning outcomes that increase in each cycle is an indicator of this. Although still lower than the cycle average of 69.69%, there was an increase in student learning outcomes throughout Cycle I. The introduction of Cycle II led to an overall increase in student learning outcomes of 90.90% of all students.